Medical therapy for secondary prevention of ischemic stroke - Goldstein, Larry (Henry Stewart Talks, 2008)
Risk of recurrent stroke, Lifestyle modification, Platelet antiaggregant therapy; aspirin, clopidogrel, aspirin plus sustained-release dypiridamole, Antihypertensive therapy, Lipid lowering therapy
Archived at 2018/12/10